HUBUNGAN STRUKTUR MODAL DAN KEPUTUSAN INVESTASI PADA PERUSAHAAN MANUFAKTUR - Risa Rolita (Jurnal Keuangan dan Perbankan, 2014)
The background of this study was begun with the manufacturing company needs capital to continually improvetheir performance and investors needs to look at the capital structure to determine their decision to invest. Thepurpose of this research was to know the relation between capital structure and investment decisions in ManufacturingCompany listed on the Indonesia Stock Exchange during six years (2008-2013). This study was a causalresearch. Sampling technique used purposive sampling method. Adjusted R2 test was used to measure the modelcapability in explaining the variation of dependent variable. T-test was used to test the partial regression coefficientwith a significance level of 5%. Capital structure was represented by Debt to Asset Ratio (DAR), Debt toEquity Ratio (DER), Long term Debt to Asset Ratio (LDAR), Long term Debt to Equity Ratio (LDER), Equity toAsset Ratio (EAR). Investment decision was represented by changes of Fixed Asset Ratio (AT Ratio). The resultof this research was DAR and DER gave significant effect on investment decisions.